Molecular classification and outcomes in pediatric aplastic anemia with myeloid neoplasm-associated gene variants - Li, Danni; Liao, Meiling; Liu, Yuye; Zhang, Luying; Hong, Yingxue; Guo, Yuxia; Guan, Xianmin; Dou, Ying; Wen, Xianhao (Frontiers in Pediatrics, 2025)
BackgroundThe genetic variations in aplastic anemia (AA) patients are closely related to clonal hematopoiesis, but there is limited research on this topic in children with AA. The aim of this study is to investigate the molecular classification and outcomes of children with AA combined with myeloid neoplasm-associated gene variants.MethodsThe clinical features, types of gene variants, mechanisms of action of the mutated genes, and correlations between gene variants and the outcomes of AA patients with myeloid neoplasm-associated gene variants were retrospectively analyzed.ResultsForty-six AA patients with myeloid neoplasm-associated gene variants were included, and a total of 20 gene variants were identified. The most frequent variant affected TET2 (9 patients, 19.6%), followed by ASXL1 (5 patients, 10.9%) and MPL (5 patients, 10.9%). Other variants, in descending order, affected TERT (4 patients); SH2B3, FLT3, ETV6, and JAK2 (3 patients each); BCOR, BCORL1, TP53, KIT, and SF3B1 (2 patients each); and CALR, GATA2, RUNX1, CBL, IDH1, IDH2, and WT1 (1 patient each). Six patients had 2 gene variants. The original mechanisms of action of the mutated genes mainly involved epigenetics and signal transduction pathways; both groups of genes were affected in 39.1% (18/46) of the patients. The difference in the efficacy of immunosuppressive therapy (IST) among the different gene groups was not significant. Disease severity (P = 0.046) and hematological response at 3 months (P = 0.002), 6 months (P = 0.001), 9 months (P = 0.001), and 1 year (P = 0.001) were important factors affecting survival time, but genotype was not. None of the patients experienced clonal evolution by the end of the follow-up cut-off time.ConclusionIn patients with AA combined with myeloid tumor neoplasm-associated gene variants, TET2, ASXL1 and MPL variants were the most frequently observed and primarily involved epigenetics and signal transduction pathways. There was no significant difference in the efficacy of IST among patients with different gene variants. Survival time was associated with disease severity, and the development of a hematological response—particularly when achieved at 3 months—was an independent key factor, whereas genotype was not.